Rising Chinese Influence in the Middle East: Implications for the Israel-Palestine Conflict (Al-NASR, 2024)
China’s interest in the Middle East region is not new yet the execution of initiatives, is. Chinese involvement in undertaking the Resource diplomacy in the midst of Eastern region outlines the healthy relationship of producer and consumer governments in the political cum economical arena. The strength of Chinese influence is based on "Non-interference" policy. In addition, Beijing has been successful in consciously positioning itself as a mediator in the conflict and crises prone region of Middle East. Further, the paper tries to establish how much Chinese influence can push, for the solution of Israel-Palestine conflict.(This research paper will analyze the potential impacts of an omni-potent China in the region. It will assess the various ways in which China's presence and involvement has changed the power dynamics of the region. Further, potentials and positive probabilities of greater Chinese involvement have been explored. Lastly, it will examine if the Israel-Palestine conflict could be affected by China's increased presence and influence in the Middle East)
Keywords: China; Chinese Policy; Non-military approach; Middle East; Economy; Israel; Palestine-Issue; Belt & Road Initiative (BRI); Islamic Economics